2017
DOI: 10.1002/jcp.25909
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional culture of buffalo granulosa cells in hanging drop mimics the preovulatory follicle stage

Abstract: Granulosa cell (GC) culture models mimicking the intrafollicular environment are limited. Such models have a great potential in reproductive toxicity studies. The buffalo, a monovulatory species like humans, could be a better model than polyovulatory rodents. Therefore, we targeted the development and characterization of three-dimensional (3D) culture systems for buffalo GCs. The GCs from small ovarian follicles (SF) maintained the CYP19 gene expression for 144 hr in a 2D culture system. Hence, GCs from SF wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 18 publications
1
18
1
Order By: Relevance
“…Three‐dimensional in vitro culture of the buffalo granulosa cells was carried out under serum free conditions. Typical spheroids of granulosa cells were observed in hanging drop method (Figure ) as reported earlier . After 144 h, these spheroids were treated with LPS for 2 h, 6 h, 12 h and, 24 h to study the effect of LPS on CYP19 gene expression.…”
Section: Resultsmentioning
confidence: 90%
“…Three‐dimensional in vitro culture of the buffalo granulosa cells was carried out under serum free conditions. Typical spheroids of granulosa cells were observed in hanging drop method (Figure ) as reported earlier . After 144 h, these spheroids were treated with LPS for 2 h, 6 h, 12 h and, 24 h to study the effect of LPS on CYP19 gene expression.…”
Section: Resultsmentioning
confidence: 90%
“…It is well known that FSH and IGF1 induced steroidogenesis and proliferation of GC is obligatory for ovarian follicle development in many mammals, including cows 25,26 . Therefore supplementation of FSH and IGF1 is universally practiced for GC cultures, especially for attaining an "estradiol active" phenotype [27][28][29][30][31] . In the present study, treatment of GC with physiologically relevant doses of FSH (20 ng/ml) and IGF1 (25 and 50 ng/ml) independently induced the mRNA expression of HIF1A.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore the culture duration for 1 week was somehow long enough to maintain cells and marker gene expression in a higher fold change (Hatzirodos et al, 2017). Furthermore, these data indicated that the cultured GCs did not transform into luteinizing cells, because GCs cultured from all groups still expressed a considerable amount of FSHR and CYP19 mRNAs (Portela et al, 2010;Monga et al, 2011;Yadav et al, 2018). Profiling of differently sized in vitro cultured and in vivo buffalo GCs…”
Section: Discussionmentioning
confidence: 93%